Program Pemberian Kompensasi Pegawai Dalam Mendukung Tujuan Organisasi - Sunarta Sunarta (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2021)
Abstract Compensation programs need to be aligned with organizational policies and objectives. This article is a literature review on employee compensation programs in support of organizational policies and goals. Organizations can use a combination of fixed-variable compensation, direct-indirect compensation according to organizational goals. Fixed compensation is more appropriate for routine work, whereas variable compensation is more appropriate for behavioral incentives and performance-based management. The amount of direct compensation will provide autonomy for employees in spending their family needs, however, it does not guarantee employees to allocate it, such as for: education and training costs, sports, health insurance, old age insurance, recreation. These costs are more suitable for indirect compensation. Organizations can consider the amount of compensation both in planning, evaluation through several factors, namely internal employees, organizational environment, and external environment. Keyword: planning program, compensation, fixed-variable compensation, and organization.